Foot problem and occurrence (Journal of the College of Basic Education, 2023)
This problem is considered one of the most important problems that research and studies revolved around.All philosophers and theologians are Muslims.... Many of the speakers believed that the solution to thisThe problem leads to the knowledge of the Almighty....Here is an attempt to study antiquity and occurrence, and I will follow this research with a study of the necessary and the possible.And the impossible, and by this I have conducted a study of the evidence of occurrence and necessity, and God is the conciliator.